The relationship between healthy eating motivation and protein intake in community-dwelling older adults with varying functional status - Rempe, Hanna; Sproesser, Gudrun; Hannink, Anne; Skurk, Thomas; Brandl, Beate; Hauner, Hans; Renner, Britta; Volkert, Dorothee; Sieber, Cornel; Freiberger, Ellen; Kiesswetter, Eva (Nutrients, 2020)
In older adults, the relationship between healthy eating motivation (HEM) and protein intake as key component of a healthy diet is poorly understood. Therefore, we investigate the association of HEM with (1) total protein intake and (2) intake of different protein sources in older adults with varying functional status. In this cross-sectional study including 250 adults (≥70 years), we assessed HEM with “The Eating Motivation Survey” and protein intake by 7-day food records. In addition, gender, age, Body Mass Index (BMI), energy intake and functional status were considered. Regression analyses revealed that HEM was neither related to total (β = −0.02; p = 0.723) nor to relative protein intake (β = 0.04; p = 0.370). Notwithstanding this, participants with stronger HEM showed lower intake of protein from meat and meat products (β = −0.14; p = 0.018), higher intake of overall plant-based protein (β = 0.11; p = 0.032), protein from fruit and vegetables (β = 0.20.; p = 0.002) and from pulses, nuts an seeds (β = 0.16; p = 0.016). Our findings suggest HEM as a valuable indicator for intake of distinct protein sources. However, since HEM is not related to total protein intake, the importance of sufficient protein consumption should be emphasized by promoting healthy eating, regardless of self-perceived HEM.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Functional status; Healthy eating motivation; Older adults; Protein intake; Protein sources